Molding human business leaders - what business school instructors can learn from quantum physics - Salleh, Arfah; Ahmad, Aziuddin (Islamic Bank Training and Research Academy, Islamic Bank Bangladesh Limited, 2009)
The global financial meltdown has brought to the fore the profound need for business schools to change in the way they educate and train their graduates. Making reference to the new science of quantum physics, this article examines the issue of accountability and governance among business school instructors in discharging their duties to mold their graduates into human business leaders: leaders who actualize rightness-of-action. Quantum physics parallels not only the fundamentals of Islamic tradition, but also Eastern spiritual beliefs and native communities. This article also underscores the relevance of the new scientific worldview of an interconnected universe in understanding the changing landscape of business; and establishes that the foundations of classical mechanistic Newtonian-Cartesian science are no longer appropriate in today’s knowledge-based economy. In order to appreciate the underpinnings of business education, we go backward in origin into the past to learn of the business philosophy that has shaped today’s business and the meaning of leadership. The way forward for business school instructors to bring back the relevance of business schools in molding future business leaders who will actualize authentic leadership as a human is deliberated.